2013
DOI: 10.1007/s00414-013-0847-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of southern Chinese Han and Brazilian Caucasian mutation rates at autosomal short tandem repeat loci used in human forensic genetics

Abstract: The short tandem repeat (STR) loci used in human genetic studies are characterized by having relatively high mutation rates. In particular, to ensure an appropriate evaluation of genetic evidence in parentage and forensic analyses, it is essential to have accurate estimates of the mutation rates associated with the commonly used autosomal and sex chromosome STR loci. Differences in STR mutation rates between different ethnic groups should also be determined. Mutation data from two laboratories working with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…According to AABB report in 2008 , the mutation rate of Penta‐E is only 0.26 × 10 −3 and the study of Brazilian Caucasian population also gets similar statistics . In contrast, our study shows the mutation rate of Penta‐E is 2.79 × 10 −3 , which is much higher than other populations.…”
Section: Resultssupporting
confidence: 58%
“…According to AABB report in 2008 , the mutation rate of Penta‐E is only 0.26 × 10 −3 and the study of Brazilian Caucasian population also gets similar statistics . In contrast, our study shows the mutation rate of Penta‐E is 2.79 × 10 −3 , which is much higher than other populations.…”
Section: Resultssupporting
confidence: 58%
“…We reasonably speculated that there existed discrepancy of the miRNA expression profiles between the Asian and Caucasian. Differences in gene mutation rates between different ethnic groups have been verified in previous research [56]. Anyway, it is necessary to validate the findings in more LSCC tissue samples.…”
Section: Discussionmentioning
confidence: 71%
“…3B, *: p<0.01). Sun et al reported that the paternal mutations are more than maternal mutations in Guangdong Province of China and even the average ratio of male/female mutations can reach 3.8:1 (Sun et al 2014). Our results are consistent with her conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, some reports have studied the mutation of STR in some areas and districts of China (Lei et al 2014; Meng et al 2015; Sun et al 2014; Yan et al 2006; Yin et al 2015), but the scale of data on mutation rates of STR including the number of tested case, scope and area is still limited. Meanwhile, there are limited data of human population genetics from STR mutation.…”
Section: Introductionmentioning
confidence: 99%